Diagnostic value of transvaginal contrast-enhanced ultrasound in identifying benign and malignant endometrial lesions and assessing myometrial invasion - Fang Guo; Yulin Yan; Chengsheng Huang; Xia Wang; Xing Wu; Yanli Xu; Tao Ying (Ultrasonography, 2024)
Purpose The objective of this study was to evaluate the diagnostic value of transvaginal contrast-enhanced ultrasound (CEUS) in differentiating benign from malignant endometrial lesions and assessing the extent of myometrial invasion. Methods A total of 70 patients who underwent surgery for endometrial lesions at the authors’ hospital were selected. Transvaginal ultrasound examination and CEUS were performed for quantitative and qualitative analysis. Based on the CEUS results, an International Federation of Gynecology and Obstetrics (FIGO) disease grade was assigned and compared with pathological findings. Results Postmenopausal vaginal bleeding is a key clinical manifestation of endometrial carcinoma. Among the patients with endometrial carcinoma, compared with normal myometrium, the lesion areas exhibited a greater rate of rise (defined as enhanced intensity divided by enhancement time) and a shorter half-clearance time (P<0.05). These findings suggest that in endometrial carcinoma, the contrast agent displays a "fast-in/fast-out/hyperenhancement" perfusion pattern. In contrast, the characteristic perfusion pattern for benign endometrial lesions is low enhancement (P<0.05). The diagnostic accuracy of CEUS in detecting myometrial invasion was 88% (22 of 25 cases). Conclusion Transvaginal CEUS is a practical and effective diagnostic imaging method for distinguishing between benign and malignant endometrial lesions. It can also be used to evaluate the depth of myometrial invasion in patients with early-stage endometrial carcinoma.